Effects of nitrogen stress and nitrogen form ratios on the bacterial community and diversity in the root surface and rhizosphere of Cunninghamia lanceolata and Schima superba - Wang, Yanru; Li, Xiaoyu; Quan, Xiaoqiang; Liang, Haiyan; Wang, Lidong; Yan, Xiaoli (Frontiers in Plant Science, 2023)
Background The bacterial communities of the root surface and rhizosphere play a crucial role in the decomposition and transformation of soil nitrogen (N) and are also affected by soil N levels and distribution, especially the composition and diversity, which are sensitive to changes in the environment with high spatial and temporal heterogeneity of ammonium N (NH4+-N) and nitrate N (NO3--N). Methods One-year-old seedlings of Cunninghamia lanceolata and Schima superba were subjected to N stress (0.5 mmol L-1) and normal N supply (2 mmol L-1), and five different N form ratios (NH4+-N to NO3--N ratio of 10:0, 0:10, 8:2, 2:8, and 5:5) were created. We analyze the changes in composition and diversity of bacteria in the root surface and rhizosphere of two tree species by high-throughput sequencing. Results Differences in the composition of the major bacteria in the root surface and rhizosphere of C.lanceolata and S. superba under N stress and N form ratios were not significant. The dominant bacterial phyla shared by two tree species included Proteobacteria and Bacteroidota. Compared to normal N supply, the patterns of diversity in the root surface and rhizosphere of two tree species under N stress were distinct for each at five N form ratios. Under N stress, the bacterial diversity in the root surface was highest at NH4+-N to NO3--N ratio of 10:0 of C. lanceolata, whereas in the root surface, it was highest at the NH4+-N to NO3--N ratio of 0:10 of S. superba. The NH4+-N to NO3--N ratio of 5:5 reduced the bacterial diversity in the rhizosphere of two tree species, and the stability of the bacterial community in the rhizosphere was decreased in C. lanceolata. In addition, the bacterial diversity in the root surface was higher than in the rhizosphere under the N stress of two tree species. Conclusion The bacterial compositions were relatively conserved, but abundance and diversity changed in the root surface and rhizosphere of C. lanceolata and S. superba under N stress and different N form ratios. The heterogeneity of ammonium and nitrate N addition should be considered for N-stressed environments to improve bacterial diversity in the rhizosphere of two tree species.